2022
DOI: 10.1021/acs.jafc.1c07877
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin Alleviates Asthma Airway Inflammation by Regulating Mitophagy and Mitochondrial Apoptosis

Abstract: Bronchial asthma poses a considerable burden on both individual patients and public health. Sesamin is a natural lignan that relieves asthma. However, the potential regulatory mechanism has not been fully validated. In this study, we revealed the mechanism of sesamin in inhibiting airway inflammation of asthma. In cockroach extract (CRE)-induced asthmatic mice, sesamin efficiently inhibited inflammatory cell infiltration, expressions of total and CRE-specific IgE in serum, and inflammatory cytokines (including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Disorder of the redox system and inflammation can promote apoptosis [ 114 , 115 ]. In this study, colonic epithelial cells of mice showed mitochondrial damage after PP-MP exposure, and TUNEL results suggested apoptosis of colonic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Disorder of the redox system and inflammation can promote apoptosis [ 114 , 115 ]. In this study, colonic epithelial cells of mice showed mitochondrial damage after PP-MP exposure, and TUNEL results suggested apoptosis of colonic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…[77,78] Sesamin (NuBBE ID: 1416) has been studied in treating asthma, Parkinson's and Alzheimer's diseases, and several types of cancers, including breast, cervical, gallbladder and colon cancer. [79][80][81][82][83][84][85] In drug discovery and development process pharmacokinetics plays a vital role to explore lead compounds through optimizing their ADMET properties. In order to pass clinical trials subsequently the final approval of drug candidate, pharmacokinetic properties of the drug candidate and pharmacological action on the body, organ and tissue must be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Asaranin (NuBBE ID: 1420) has been previously reported to have anticancer effects against ovarian cancer and act as an immunomodulatory [77,78] . Sesamin (NuBBE ID: 1416) has been studied in treating asthma, Parkinson's and Alzheimer's diseases, and several types of cancers, including breast, cervical, gallbladder and colon cancer [79–85] …”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have found that excessive mitochondrial autophagy promotes the development of in ammatory diseases [54] . For example, Bai [55] et al reported that sesamin alleviated asthma by inhibiting mitophagy and mitochondrial apoptosis. In addition, chronic CS exposure has been reported to induce mitochondrial autophagy, leading to the accumulation of nuclear mitochondria in human lung epithelial cells and broblasts [56] .…”
Section: Discussionmentioning
confidence: 99%